2010
DOI: 10.1021/jm101251q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and SAR of 5-(3-Chlorophenylamino)benzo[c][2,6]naphthyridine-8-carboxylic Acid (CX-4945), the First Clinical Stage Inhibitor of Protein Kinase CK2 for the Treatment of Cancer

Abstract: Herein we chronicle the discovery of CX-4945 (25n), a first-in-class, orally bioavailable ATP-competitive inhibitor of protein kinase CK2 in clinical trials for cancer. CK2 has long been considered a prime cancer drug target because of the roles of deregulated and overexpressed CK2 in cancer-promoting prosurvival and antiapoptotic pathways. These biological properties as well as the suitability of CK2's small ATP binding site for the design of selective inhibitors, led us to fashion novel therapeutic agents fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
232
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(245 citation statements)
references
References 60 publications
12
232
1
Order By: Relevance
“…However, since a number of CK2 substrates have been existed, many CK2 inhibitors have been developed and widely utilized (Pagano et al, 2004;2008;Prudent et al, 2009;Sarno et al, 2001;Zien et al, 2005), the validation of 'druggability' of kinase inhibitors is very important in a various CK2-mediated regulatory mechanism. Previous studies identified CX-4945 as a CK2 inhibitor that regulates human cancer cell survival and angiogenesis Pierre et al, 2011a;2011b;Siddiqui-Jain et al, 2010), and our recent study showed that CX-4945 has favorable pharmacokinetic characteristics (Son et al, 2013). Since several studies have reported the possible involvement of CK2 and its effect Akt in bone metabolism (Bragdon et al, 2010;Moon et al, 2012), here we evaluated and found the antiosteoclastogenic and anabolic activity of CX-4945; CX-4945 inhibited the RANKL-induced osteoclast differentiation accompanied with suppression of Akt/NFATc1 signaling axis, but it enhanced the BMP-2-induced osteoblast differentiation via the ERK1/2-Smad signaling axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since a number of CK2 substrates have been existed, many CK2 inhibitors have been developed and widely utilized (Pagano et al, 2004;2008;Prudent et al, 2009;Sarno et al, 2001;Zien et al, 2005), the validation of 'druggability' of kinase inhibitors is very important in a various CK2-mediated regulatory mechanism. Previous studies identified CX-4945 as a CK2 inhibitor that regulates human cancer cell survival and angiogenesis Pierre et al, 2011a;2011b;Siddiqui-Jain et al, 2010), and our recent study showed that CX-4945 has favorable pharmacokinetic characteristics (Son et al, 2013). Since several studies have reported the possible involvement of CK2 and its effect Akt in bone metabolism (Bragdon et al, 2010;Moon et al, 2012), here we evaluated and found the antiosteoclastogenic and anabolic activity of CX-4945; CX-4945 inhibited the RANKL-induced osteoclast differentiation accompanied with suppression of Akt/NFATc1 signaling axis, but it enhanced the BMP-2-induced osteoblast differentiation via the ERK1/2-Smad signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…CX-4945 was developed with the intention of using it in combination with diverse anti-cancer drugs, and it has been investigated for various cancer indications. Preliminary reports showed that CX-4945 has potent anti-proliferative, anti-angiogenic and anti-inflammatory activity via inhibition of CK2-Akt mediated signaling pathways in human cancer cells (Pierre et al, 2011a;2011b;Siddiqui-Jain et al, 2010). A recent study showed that activation of Akt induces osteoclastogenesis via GSK3β/NFATc1 signaling and that bone morphogenetic protein (BMP)-2-induced CK2 regulates osteoblast differentiation via Smad1/5/8 signaling (Bragdon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6 The recent discovery of CX-4945, a selective, orally available inhibitor of CK2 by researchers from Cylene, represents an important first step in evaluating the clinical potential of this novel target in man. 7 We have recently described the design of a series of conformationally constrained inhibitors of CK2 containing the pyrazolo[1,5-a]pyrimidine nucleus.8 Members of this series of compounds exhibited potent inhibition of the enzyme, possessed a high degree of kinase selectivity, and depleted cellular levels of pAKT S129 , a direct substrate of CK2 believed to hyperactivate the AKT pathway.9 Although our attempts to enhance both cellular potency and physical properties in this series were unsuccessful, these studies resulted in an understanding of the structure−property relationships within the scaffold and provided additional insights into ligand−receptor binding. In particular, we found that N-methylation of the acetamide of 1a, to give ring-constrained analogue 1b, preserved enzymatic and cellular activity.…”
mentioning
confidence: 99%
“…6 The recent discovery of CX-4945, a selective, orally available inhibitor of CK2 by researchers from Cylene, represents an important first step in evaluating the clinical potential of this novel target in man. 7 We have recently described the design of a series of conformationally constrained inhibitors of CK2 containing the pyrazolo[1,5-a]pyrimidine nucleus.…”
mentioning
confidence: 99%
See 1 more Smart Citation